CISG articles 92 and 96 reservations and global uniformity of international sales law: failure or success through compromise? - Makumbe, Ratidzo (Midlands State University, 2017)
The CISG is acclaimed world over for its success in unifying internationals sales law despite the compromises during its drafting. This thesis examines whether the compromises in the Article 92 and 96 reservations have affected the uniformity of the CISG and whether they are still relevant for the success of the Convention today. In conclusion it recommends that the declarations be withdrawn and the Convention be amended to allow for uniformity of the CISG.